Effect of electron irradiation conditions on the efficiency of defect formation in MgAl₂O₄ spinel - Kazarinov, Yu.H.; Pop, O.M.; Megela, I.G.; Popov, A.I. (Problems of Atomic Science and Technology, 2022)
The efficiency of defect formation in spinel ceramics of magnesium aluminate (MgAl₂O₄) under electron irradiation has been determined. A strong effect of cooling on the concentration of residual defects was revealed. When using electrons with energies above the giant dipole resonance for Mg, Al, O and cooling the sample with an air-blown aluminum radiator, a total increase in the efficiency of F-center formation by a factor of 4.3 was obtained. Визначено ефективність дефектоутворення при електронному опроміненні в кераміці магній-алюмінієвої шпінелі (MgAl₂O₄). Виявлено сильний вплив охолодження на концентрацію залишкових дефектів. При використанні електронів з енергією вище гігантського дипольного резонансу для Mg, Al, O та охолодженні зразка алюмінієвим радіатором з повітряним обдувом отримано сумарне підвищення ефективності формування F-центрів у 4,3 рази.